Sulfur cathode integrated with multileveled carbon nanoflake-nanosphere networks for high-performance lithium-sulfur batteries. (10th February 2017) - Li, S.H.; Wang, X.H.; Xia, X.H.; Wang, Y.D.; Wang, X.L.; Tu, J.P.
Graphical abstract: Abstract: Tailored design/construction of high-quality sulfur/carbon composite cathode is critical for development of advanced lithium-sulfur batteries. We report a powerful strategy for integrated fabrication of sulfur impregnated into three-dimensional (3D) multileveled carbon nanoflake-nanosphere networks (CNNNs) by means of sacrificial ZnO template plus glucose carbonization. The multileveled CNNNs are not only utilized as large-area host/backbone for sulfur forming an integrated S/CNNNs composite electrode, but also serve as multiple carbon blocking barriers (nanoflake infrastructure andnanosphere superstructure) to physically confine polysulfides at the cathode. The designedself-supported S/CNNNs composite cathodes exhibit superior electrochemical performances with high capacities (1395 mAh g −1 at 0.1C, and 769 mAh g −1 at 5.0C after 200 cycles) and noticeable cycling performance (81.6% retention after 200 cycles). Our results build a new bridge between sulfur and carbon networks with multiple blocking effects for polysulfides, and provide references for construction of other high-performance sulfur cathodes.